Mixed adenoneuroendocrine carcinoma of the esophagogastric junction: a case report - Miho Yamamoto; Soji Ozawa; Kazuo Koyanagi; Junya Oguma; Akihito Kazuno; Yamato Ninomiya; Kentaro Yatabe; Kazuhito Hatanaka (Surgical Case Reports)
Abstract Background Mixed adenoneuroendocrine carcinoma (MANEC) is a tumor of the gastrointestinal tract that contains both exocrine and endocrine components, with each component exceeding 30% of the total tumor area. Because MANECs are exceedingly rare, no therapeutic strategies have been established yet. Case presentation An 81-year-old man was referred to our hospital with a 5-month history of dysphagia. Esophagogastroduodenoscopy revealed an ulcerated mass in the lower thoracic esophagus, extending up to the esophagogastric junction (33 to 40 cm from the incisors). The initial biopsy diagnosis was adenocarcinoma. Computed tomography revealed no evidence of lymph node or distant metastasis. The patient was treated by thoracoscopic esophagectomy with three-field lymph node dissection and gastric tube reconstruction via a posterior mediastinal approach, under the diagnosis of esophagogastric junctional cancer (T3N0M0, stage IIA). Histopathological examination revealed two distinct components, namely, a neuroendocrine carcinoma component and an adenocarcinoma component, and the patient was diagnosed as having mixed adenoneuroendocrine carcinoma (MANEC). He presented with liver metastasis 6 months after the surgery. Thereafter, the tumor became even more aggressive, and the patient died 8 months after the surgery. Conclusions We report a patient with MANEC of the esophagogastric junction. Close attention should be paid to such patients, as MANEC can be a highly aggressive tumor, showing rapid progression. In the treatment of MANEC, it is necessary to carefully consider the pathological features in each individual case.